(untitled) (Applied Biological Research, 2012)
A field experiment was conducted during 2009-10 and 2010-11 at Research Farm, Division of Agronomy, SKUAST-K, Shalimar (J&K) to assess the influence of sowing dates, fertility levels and cutting management on yield and quality of forage oat. Early sowing gave higher green and dry fodder yields while high crude protein, low crude fibre and high ash contents were observed in oats sown on October 10. Green fodder and dry fodder yields and crude protein content increased with increase in fertility level up to 150 kg N + 70 kg P2O5 + 40 kg K2Oha-1. Double cut crop gave higher forage yield and better quality traits as compared to single cut crop.